Untangling Paradox: A Humanitarian Perspective on Nuclear Weapons Trade in Non-Proliferation Ambition - Ferdianty, Shavina Putri; Azaria, Davilla Prawidya (Hang Tuah Law Journal, 2024)
The emerging issue of the legality of nuclear weapons trade by the state remains unclear as the use of nuclear weapons itself. Nuclear weapons are perceived either as a threat to human lives or a potential guarding system for a state. Contrary for the latter, states have the enormous ambition to establish non-proliferation of nuclear weapons to justify its use. Trade practice is prone to be bent as a tool to develop nuclear weapons programs. This research is a normative legal research that uses statutory and conceptual approaches. By examining both legal instruments and fundamental principles of humanitarian law are able to elucidate the paradox of non-proliferation and nuclear weapons trade conducted by states. Humanitarian principles are an adequate fundamental basis to examine the legal uncertainty of nuclear weapons use. Jus ad bellum defined that nuclear weapons violate proportionality and precautionary principles. The study argues for a particular legally binding instrument to prohibit nuclear weapons as a subject to international trade regime. Furthermore, the International Atomic Energy Agency as an authorized institution must be strengthened in order to maintain the peaceful use of nuclear energy as well as programs developed by states.